"The Script Does Not Respond" ‐ Arabic Script's Difficulties in the Digital Realm. A Visual Approach. Issue 2 (31st December 2020) - Kokoschka, Alina
Abstract: This article examines different layers of the problematic visual representation of Arabic as a writing system in the digital realm. It starts with the often false, sometimes severely distorted representations of Arabic script. Although most obvious in daily office work and strolls through Latin‐Arabic Linguistic Landscapes, this phenomenon has not yet been systematically looked into. The many unintended and often unnoticed misrepresentations that lead to illegible texts and reader‐unfriendly websites are only the tip of the iceberg. They give visibility to a fundamental lack of script‐specific visual organization of knowledge in digital surroundings and the virtual absence of Arabic‐based digital infrastructure. These phenomena may be examined as a case in point of Latin dominance . This article is a visual account. It investigates the common faults from a typographic and aesthetic perspective against the background of different layers of Arabic scribal tradition. It, therefore, moves from single letters and Arabic script's specificities over to bi‐scriptual encounters and then to more complex text arrangements in websites, programming, and manuscripts. While research in this very field necessarily focuses on deficiencies and problems, possible solutions will also be presented and discussed .